An assessment of the inherent reliability of SANS 10162-2 for cold-formed steel columns using the direct strength method - West-Russell, Michael Alexander (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.